Impact of Income Tax, Tax Haven Utilization, and Foreign Ownership on Transfer Pricing Practices - Purwitasari, Ni Putu Mila; Merkusiwati, Ni Ketut Lely Aryani (E-Jurnal Akuntansi; Vol 34 No 9 (2024)DO - 10.24843/EJA.2024.v34.i09.p02, 2024)
Transfer pricing is a significant concern in accounting and taxation because it is viewed as a strategic tool that can enable companies to gain a competitive advantage. This study aims to provide empirical evidence on the impact of income tax, tax haven utilization, and foreign ownership on transfer pricing practices. The research focuses on manufacturing companies listed on the Indonesia Stock Exchange from 2020 to 2022. A purposive sampling technique was employed to select the sample, resulting in the collection of 96 observational data points. The data were analyzed using multiple linear regression. The findings indicate that income tax exerts a positive influence on transfer pricing, whereas tax haven utilization and foreign ownership do not have a significant impact on transfer pricing practices. Keywords: Transfer Pricing; Income Tax; Tax Haven Utilization; Foreign Ownership